2014
DOI: 10.1152/ajpregu.00118.2014
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin in the ventromedial hypothalamic nucleus reduces feeding and acutely increases energy expenditure

Abstract: Noble EE, Billington CJ, Kotz CM, Wang C. Oxytocin in the ventromedial hypothalamic nucleus reduces feeding and acutely increases energy expenditure. Am J Physiol Regul Integr Comp Physiol 307: R737-R745, 2014. First published July 2, 2014; doi:10.1152/ajpregu.00118.2014.-Central oxytocin reduces food intake and increases energy expenditure. The ventromedial hypothalamic nucleus (VMN) is associated with energy balance and contains a high density of oxytocin receptors. We hypothesized that oxytocin in the VMN i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 64 publications
5
77
2
2
Order By: Relevance
“…Overall, the data indicate that chronic subcutaneous administration of oxytocin, at doses that reduce weight gain and food intake in chow-fed rats, is unlikely to elicit nausea. These findings extend other reports showing that acute bolus injections of oxytocin into the CNS or periphery fail to increase kaolin intake (103) or elicit a conditioned taste aversion (42,63,103).…”
Section: Study 9: Effects Of Chronic Subcutaneous Oxytocin Infusions supporting
confidence: 89%
See 2 more Smart Citations
“…Overall, the data indicate that chronic subcutaneous administration of oxytocin, at doses that reduce weight gain and food intake in chow-fed rats, is unlikely to elicit nausea. These findings extend other reports showing that acute bolus injections of oxytocin into the CNS or periphery fail to increase kaolin intake (103) or elicit a conditioned taste aversion (42,63,103).…”
Section: Study 9: Effects Of Chronic Subcutaneous Oxytocin Infusions supporting
confidence: 89%
“…The mechanism underlying these effects may involve outgoing polysynaptic sympathetic nervous system projections from PVN oxytocin neurons to both inguinal (86) and epididymal white adipose tissue (86,89). With respect to the question of which receptor populations contribute to the effects of oxytocin to impact energy expenditure, acute microinjection of oxytocin into the median raphe increases both heart rate and body temperature in mice (102), and oxytocin administration into the VMH increases short-term energy expenditure in rats (63). Evidence that adeno-associated viral expression of OTRs into the VMH/DMH of OTR null mice restores impairments in cold-induced thermogenesis (45) and corrects defects in ␤3-and ␣2-adrenceptor mRNA expression in interscapular brown adipose tissue, strengthens the link between OTRs in these areas and control of energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OTR in this region appears to be a common feature of hystricognath rodents measured to date, including guinea pigs and tuco-tucos as well as mole-rats, while its presence may be more variable and species-specific in myomorphic rodents (Tribollet et al, 1992;Beery et al, 2008). Oxytocin in the VMH decreases feeding and promotes activity in rats (Noble et al, 2014). While it remains to be tested whether oxytocin in the VMH has these effects in naked mole-rats, they might be beneficial to species that rely on subterranean group foraging for survival (Brett, 1991b).…”
Section: Otr Binding Distribution and Densitymentioning
confidence: 94%
“…We found that mice showed increased energy expenditure with decreased respiratory quotient (RQ) during the light phase of the treatment period [23]. The RQ decrease by oxytocin treatment was also confirmed in rats, monkeys, and humans [25,32,34,35,135]. This reduction of BW by oxytocin may also be mediated by the induction of diet-induced thermogenesis [31,47].…”
Section: Clinical Implications Of Oxytocinmentioning
confidence: 64%